Correction: Using a functional C84 monolayer to improve the mechanical properties and alter substrate deformation. Issue 65 (16th July 2015) - Lee, Wen-Jay; Ho, Mon-Shu; Huang, Chih-Pong; Chou, Che-Fu; Tsai, Jyun-Hwei; Su, Wan-Sheng
<x xml:space="preserve">Abstract</x> Correction for 'Using a functional C84 monolayer to improve the mechanical properties and alter substrate deformation' by Wen-Jay Lee et al., RSC Adv., 2015, 5, 47498–47505.